2008 49th Annual IEEE Symposium on Foundations of Computer Science 2008
DOI: 10.1109/focs.2008.18
|View full text |Cite
|
Sign up to set email alerts
|

Some Results on Greedy Embeddings in Metric Spaces

Abstract: Geographic Routing is a family of routing algorithms that uses geographic point locations as addresses for the purposes of routing. Such routing algorithms have proven to be both simple to implement and heuristically effective when applied to wireless sensor networks. Greedy Routing is a natural abstraction of this model in which nodes are assigned virtual coordinates in a metric space, and these coordinates are used to perform point-to-point routing.Here we resolve a conjecture of Papadimitriou and Ratajczak … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 20 publications
1
17
0
Order By: Relevance
“…They also showed that any planar 3-connected newtork has a greedy embedding in 3 dimensions, for which an embedding algorithm was described in [10]. The Papadimitriou-Ratajczak conjecture was very recently, settled by Moitra and Leighton [27] who present a polynomial-time algorithm for constructing a greedy embedding of a given 3-connected planar graph. In this paper, we study the embedding of a combinatorial UDG where only the connectivity information but no position information of the vertices is given.…”
Section: Related Workmentioning
confidence: 96%
“…They also showed that any planar 3-connected newtork has a greedy embedding in 3 dimensions, for which an embedding algorithm was described in [10]. The Papadimitriou-Ratajczak conjecture was very recently, settled by Moitra and Leighton [27] who present a polynomial-time algorithm for constructing a greedy embedding of a given 3-connected planar graph. In this paper, we study the embedding of a combinatorial UDG where only the connectivity information but no position information of the vertices is given.…”
Section: Related Workmentioning
confidence: 96%
“…Our question is somewhat related to a larger question of embedding metrics into low-dimensional Euclidean spaces. Such questions have motivated a large body of work to aid the understanding of metric/graph embeddings (Kuhn et al 2010;Pemmaraju and Pirwani 2007;Krauthgamer and Lee 2007), various graph classes and special metric spaces as they relate to one another and to the complexity of various optimization problems on these special classes (Raghavan and Spinrad 2001;Nieberg et al 2008;Talwar 2004), and applications in wireless networks such as routing (Papadimitriou and Ratajczak 2005;Dhandapani 2008; Moitra and Leighton 2008;Goodrich and Strash 2009) and localization (Bulusu et al 2000;Bruck et al 2005;Aspnes et al 2004;Nagpal et al 2003). One might think that if a feasible realization of these combinatorial objects can be found, then one can (indirectly) apply the shifting strategy on the objects to obtain good approximation algorithms.…”
Section: Introductionmentioning
confidence: 99%
“…In an upward drawing [6,7], every directed path is monotone with respect to the positive y direction. Even more related to the monotone drawings are the greedy drawings [2,14,16]. In a greedy drawing, for any two vertices u, v, there exists a path P uv from u to v such that the Euclidean distance from an intermediate vertex of P uv to the destination v decreases at each step.…”
Section: Introductionmentioning
confidence: 99%